The impact of the diversity of the board of directors in the adoption of risk management and control practices - Godoy Ávila, Pablo Esteban (2024)
Fil: Godoy Ávila, Pablo Esteban. Universidad de Talca. Centro de Investigación y Estudios Contables; Chile.